Business Transformation and the Performance of Manufacturing Frms in Nigeria - Samson, Audu (MultiTech Publisher, 2024)
The business atmosphere is increasingly becoming competitive due to the reality of global dynamics. Thus, firms especially, the manufacturing sub-sector need to adopt transformation strategies to enable them compete favorably. This study titled Business transformation and Performance of the Manufacturing Firms in Nigeria is written to examine the effect of business transformation on performance of manufacturing sub-sector in North-Central Nigeria. The population of the study was 1404 spread across the selected manufacturing firms in Nigeria. However, due to the fact that the population is large the researcher utilized the Godden sample size statistical technique to reach 302 respondents, however, only 284 respondents completed and returned their questionnaire which shows a retrieval rate of 94%. More so, the study applied research survey design, and the statistical tools applied comprised descriptive and parametric statistics. More so, the hypothesis was tested using simple linear regression analysis. The findings revealed that there is a significant positive relationship between Technological Resource application and First Pass Yield (r =.939, p-value <0.05. In view of the finding, the study concluded that there is a significant positive relationship between Business transformation and Performance of manufacturing firms in Nigeria. Anchored on the finding the study recommends that a Business Transformation techniques should be improved and periodic review be carried out in order to sustain and improve performance.